Network pharmacology combined with untargeted metabolomics reveals the intervention mechanism and compatibility of chenpi-rougui herb pair in nonalcoholic fatty liver disease - Xu, Jinlin; Li, Sen; Jin, Yuehui; Yao, Huiwen; Hu, Xu; Cao, Shan; Zhou, Huimin (Frontiers in Molecular Biosciences, 2025)
BackgroundChenpi (the dried mature peel of Citrus reticulata Blanco) and Rougui (the dried bark of Cinnamomum cassia Presl) are both edible and medicinal plants, which have therapeutic effects on nonalcoholic fatty liver disease (NAFLD). However, the underlying mechanisms necessitate further exploration. This study evaluated the prevention effect of Chenpi-Rougui herb pair (CRP) on NAFLD using an integrated strategy that combined network pharmacology with metabolomics.MethodsInitially, the components in CRP decoction were characterized by UPLC-QTOF-MS/MS. Subsequently, a high-fat diet induced NAFLD mouse model was used to assess the efficacy of CRP and its individual constituent, Chenpi and Rougui. Additionally, synergetic pathways and crucial targets for CRP therapy in NAFLD were identified using network pharmacology and serum metabolomics. Finally, real-time polymerase chain reaction (RT-PCR) was utilized to validate relevant genes.ResultsCRP exerted a more extensive prevention effect on NAFLD mice compared to the individual herb of Chenpi and Rougui. A total of 105 compounds were characterized from CRP, which were linked to 70 potential therapeutic targets for NAFLD. Thirty-two differential metabolites were identified by metabolomics, which were co-regulated by Chenpi, Rougui and CRP. Pathways associated with the intervention of herb pair in NAFLD included energy metabolism, fatty acid metabolism, glycerophospholipid metabolism, sphingolipids metabolism, arachidonic acid metabolism, sterol and bile acid metabolism. Finally, eight targets were screened through conjoint analysis and experimental verification showed that six of them including FASN, AKT1, CASP3, F2, PTGS2 and PRKCA, could be modulated by CRP in NAFLD mice. Besides, Chenpi primarily regulated FASN, AKT1, CASP3 and PRKCA, which were associated with reducing apoptosis in hepatocytes, while Rougui exceled in regulating F2 and PTGS2, closely linked to its anti-inflammatory properties. The combination of Chenpi and Rougui resulted in a broader influence on metabolites, pathways, and primary targets compared to their individual application.ConclusionThese results provided valuable insights into the compatibility mechanism of CRP for treating NAFLD, and could also improve the value of its forthcoming application and development as a natural liver protective agent.